Expert System to Detect the Level of Parental Stress in Online Learning by Using Forward Chaining Method - Susi Erlinda M. Kom; Rika Desmalita; Liya Astarilla Dede Warman (JAIA - Journal of Artificial Intelligence and Applications, 2022)
This research was aimed to make an expert system application to detect and identify the parental stress level in online learning by using the Forward Chaining method. The system was designed and implemented based on Desktop by using basic programming language. The data were collected through questionnaire consisted of 30 questions. The final score would determine the stress level of the respondents. The respondents were chosen by using random sampling technique. XAMPP data with the results obtained from 150 respondents who have educational backgrounds; elementary school (4 respondents), junior high school (6 respondents), high school (120 respondents), associate degree (11 respondents), bachelor degree (9 respondents).There were 123 respondents do not work, and 27 respondents were working parents. The findings showed that from 150 respondents there were 22% or 33 respondents were at normal level, 6% or 9 respondents were at mild level of stress, 8% or 12 respondents were at moderate level of stress, and 64% or 96 respondents were at severe level of stress. It was concluded that this application can be used to detect the parental stress level in online learning. It was also expected through the use of this application can help parents to detect their stress level earlier and find solution of it in order to avoid the negative impact of their problems.